Pengaruh TATO, ROA, DER, dan Firm Size Terhadap Return Saham - Miranti Tri Lestari; Syaiful Bahri; M. Bahril Ilmiddaviq (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study analyzes the effect of TATO, ROA, DER, and company size on stock returns of textile and garment subsector manufacturing companies listed on the IDX for the 2021-2024 period.  This research method uses a quantitative approach with a causal association design using secondary data from the financial statements of 15 companies for four years analyzed through multiple linear regression. The results showed that DER has a negative effect on stock returns, while TATO, ROA, and company size have no effect. The findings confirm capital structure, especially high leverage, adversely affects investment returns, while asset efficiency and firm size do not directly affect stock returns in industries sensitive to global conditions. The study suggests that investors should be cautious in interpreting financial signals and pay attention to capital structure factors in making investment decisions.